Antiphospholipid antibodies and growth retardation in intrauterine development - Spegiorin, L C J F; Galão, E A; De Godoy, J M P; Bagarelli, L B; Oliani, A H (Prague medical report, 2007)
The aim of this study was to evaluate the efficacy of prophylaxis using low-dose non-fractioned heparin and aspirin in the prevention of intrauterine growth restriction and low birth weights in patients suffering from antiphospholipid antibody syndrome. Intrauterine growth retardation and birth weights of 34 gestations involving 28 women with histories of multiple miscarriages and elevated antiphospholipid antibody levels were evaluated in a prospective study in the period from April 1988 to July 2004. A control group was formed of 39 women without previous history of miscarriages over a total of 40 gestations. Intrauterine growth retardation was considered when the weight of the newborn baby was below the tenth percentile for gestational age according to the fetal weight chart. Diagnosis of antiphospholipid antibodies was achieved using the ELIZA test to measure the IgG and IgM immunoglobulin levels. Evaluation of lupus anticoagulant was performed using the activated partial thromboplastin time (aPTT). Women suffering from antiphospholipid antibodies underwent prophylactic treatment during gestation with low doses of acetylsalicylic acid (100 mg daily) associated to low doses of subcutaneous heparin (5000 IU twice daily). The non-paired Student t-test, Fisher Exact and Mann-Whitney tests were used for statistical analysis with an a error of up to 5% considered acceptable. A statistically higher number of newborns suffered intrauterine growth retardation and low birth weights in the study group than in the control group. In conclusion, children of mothers suffering from antiphospholipid antibody syndrome, even those undergoing prophylactic treatment with low-dose non-fractioned heparin and aspirin, are associated to intrauterine growth retardation and low birth weights.
Keywords: antifosfolipidový syndrom; Antiphospholipid Syndrome; Pregnancy Complications; Fetal Growth Retardation; lidé; Female; Infant, Newborn; antifosfolipidové protilátky; Pregnancy; Antibodies, Antiphospholipid; těhotenství; novorozenec; růstová retardace plodu; komplikace těhotenství; ženské pohlaví; Humans